Mohammad Natsir's socio-religious and political thought - Solihin, Sohirin Mohammad (2010)
The book discusses the role of Mohammad Natsir, ex Prime Minister of Indonesia in developing the country through socio-religious and political thought. It deals with the comparative study between Western democracy and theistic democracy. In addition, his views on nationalism from the Islamic perspective are also highlighted. Moreover, Natsir also encouraged the peaceful co-existence among religious adherents in Indonesia and gave strong warning the Christianity should respect the concept of freedom of belief correctly. The concept of knowledge and the importance of promoting Arabic among Muslim youths and integration between Western and Eastern knowledge become the focus of in this book.